Role of Ultrasound and Photoacoustic Imaging in Photodynamic Therapy for Cancer. (5th March 2020) - Hester, Scott C.; Kuriakose, Maju; Nguyen, Christopher D.; Mallidi, Srivalleesha
Abstract: Photodynamic therapy (PDT) is a phototoxic treatment with high spatial and temporal control and has shown tremendous promise in the management of cancer due to its high efficacy and minimal side effects. PDT efficacy is dictated by a complex relationship between dosimetry parameters such as the concentration of the photosensitizer at the tumor site, its spatial localization (intracellular or extracellular), light dose and distribution, oxygen distribution and concentration, and the heterogeneity of the inter‐ and intratumoral microenvironment. Studying and characterizing these parameters, along with monitoring tumor heterogeneity pre‐ and post‐PDT, provides essential data for predicting therapeutic response and the design of subsequent therapies. In this review, we elucidate the role of ultrasound (US) and photoacoustic imaging in improving PDT‐mediated outcomes in cancer—from tracking photosensitizer uptake and vascular destruction, to measuring oxygenation dynamics and the overall evaluation of tumor responses. We also present recent advances in multifunctional theranostic nanomaterials that can improve either US or photoacoustic imaging contrast, as well as deliver photosensitizers specifically to tumors. Given the wide availability, low‐cost, portability and nonionizing nature of US and photoacoustic imaging, together with their capabilities of providing multiparametric morphological and functional information, these technologies are thusly inimitable when deployed in conjunction with PDT. Abstract : Here we review the role of ultrasound (US) and photoacoustic imaging in improving photodynamic therapy (PDT)‐mediated outcomes in cancer. The utility of these techniques in providing multiparametric morphological and functional information, particularly on tracking photosensitizer uptake and vascular destruction, and measuring oxygenation dynamics and the overall evaluation of tumor response, is demonstrated. We also present recent advances in multifunctional theranostic nanomaterials that improve either US or photoacoustic imaging contrast, as well as specifically deliver photosensitizers to tumors. Given the wide availability, low‐cost, portability and nonionizing nature of US and photoacoustic imaging, these technologies are inimitable when deployed in conjunction with PDT.